The kids are gonna ask - Anthony, Gretchen (Park Row Books, 2020)
"The death of Thomas and Savannah McClair's mother turns their world upside down. Raised to be fiercely curious by their grandmother Maggie, the twins become determined to learn the identity of their biological father. And when their mission goes viral, an eccentric producer offers them a dream platform: a fully sponsored podcast called The Kids Are Gonna Ask. To discover the truth, Thomas and Savannah begin interviewing people from their mother's past and are shocked when the podcast ignites in popularity. As the attention mounts, they get caught in a national debate they never asked for--but nothing compares to the mayhem that ensues when they find him." -- Provided by publisher.